Expression of mir-29a-5p, sclerostin and fetuin-A in patients with chronic kidney disease and their correlation with vascular calcification: Correlation of mir-29a-5p, sclerostin and fetuin-A with vascular calcification - Ma, Xiaoying; Sheng, Yuping; Yang, Xingmeng; Wang, Na; Zhang, Haoran; Xu, Haiping; Sun, Fuyun (Cellular and Molecular Biology, 2022)
The objective of the current study was to analyze the expression of mir-29a-5p, osteosclerotin and fetuin-A in patients with chronic kidney disease and their correlation with vascular calcification. For this purpose, 162 patients with chronic kidney disease treated in our hospital from January 2020 to January 2022 were selected retrospectively, and then 162 healthy people who underwent physical examination with our hospital in the same period were selected. The expressions of serum mir-29a-5p, sclerostin and fetuin-A were analyzed after fasting venous blood was drawn from the two groups. According to the coronary artery calcification score (CACS), patients with chronic kidney disease were divided into the calcification group (69 cases) and the non-calcification group (93 cases). The expressions of mir-29a-5p, sclerostin and fetuin-A in the two groups were analyzed, and the correlation between the three in chronic kidney disease and vascular calcification was analyzed. Results showed that compared with the control group, the expression of mir-29a-5p and sclerostin in the study group was higher, and the expression of fetuin-A was lower, the difference was statistically significant (P < 0.05); The expression of mir-29a-5p, sclerostin and fetuin-A in calcified group was higher than that in non-calcified group, and the expression of fetuin-A was lower (P < 0.05); Mir-29a-5p and sclerostin showed positive correlation (r=6.776, P=0.011); The expression of mir-29a-5p and fetuin-A showed negative correlation (r=-5.326, P=0.001); The expression of mir-29a-5p and sclerostin showed negative correlation (r=-9.677, P=0.001); Mir-29a-5p and sclerostin were positively correlated with vascular calcification (r=0.695, P=0.001; r=0.715, P=0.001), and fetuin-A was positively correlated with vascular calcification (r = -0.953, P = 0.001). Then, Mir-29a-5p, sclerostin and fetuin-A are abnormally expressed in chronic kidney disease. There is an abnormal correlation among them in chronic kidney disease, and they are correlated with vascular calcification.